2007
DOI: 10.1002/jgm.1062
|View full text |Cite
|
Sign up to set email alerts
|

Neuron‐specific delivery of nucleic acids mediated by Tet1‐modified poly(ethylenimine)

Abstract: Background-The development of minimally invasive, non-viral gene delivery vehicles for the central nervous system (CNS) is an important technology goal in the advancement of molecular therapies for neurological diseases. One approach is to deliver materials peripherally that are recognized and retrogradely transported by motor neurons toward the CNS. Tet1 is a peptide identified by Boulis and coworkers to possess the binding characteristics of tetanus toxin, which interacts specifically with motor neurons and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 47 publications
(61 reference statements)
3
77
0
Order By: Relevance
“…Small molecular weight hydrophobic molecules can be incorporated into the membrane (Ghoroghchian, et al, 2006b) and hydrophilic molecules encapsulated within the aqueous core (Lomas, et al, 2007). The polymersome can be surface-functionalized with groups that promote cellular uptake (Christian, et al, 2007;Roy, et al, 2010) or target specific cell types (Park, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Small molecular weight hydrophobic molecules can be incorporated into the membrane (Ghoroghchian, et al, 2006b) and hydrophilic molecules encapsulated within the aqueous core (Lomas, et al, 2007). The polymersome can be surface-functionalized with groups that promote cellular uptake (Christian, et al, 2007;Roy, et al, 2010) or target specific cell types (Park, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This peptide was identified based on its' homology to the tetanus toxin and it enhances neurotropism. This peptide was used by Park and colleagues to successfully target plasmid DNA the neural cells and DRG cells in vitro (Park, Lasiene et al 2007) and in vivo via an injection into lateral ventricle of mice. The tet-1 complexed plasmid was found to target adult neural progenitor cells (NPCs) (Kwon, Lasiene et al 2010).…”
Section: Non-viral Vectorsmentioning
confidence: 99%
“…Tet1-PEI synthesis-Tet1-PEI was synthesized as described previously [22]. Briefly, branched polyethylenimine (PEI, MW 25k; Sigma, St. Louis, MO) was modified with 2 mole equivalents of N-succinimidyl 3-(2-pyridyldithio)-propionate (SPDP; Pierce, Rockford, IL) in DMF for 4 hours at room temperature.…”
Section: 22mentioning
confidence: 99%
“…This peptide was shown to be internalized and transported by neurons both in vitro and in vivo [31]. Park et al demonstrated that neuron association of nonviral gene delivery vehicles is significantly increased when the vectors are modified with Tet1 peptide [22]. Tet1 peptide bearing a C-terminal cysteine was covalently linked to PEI using disulfide chemistry at ~0.6 Tet1 peptides per PEI and polyplexes were formed with plasmid DNA.…”
Section: Neuron Targetingmentioning
confidence: 99%